1994
DOI: 10.1128/aac.38.2.337
|View full text |Cite
|
Sign up to set email alerts
|

In vivo activity of ajoene against rodent malaria

Abstract: Ajoene (4,5,9-trithiadodeca-1,6,11-triene 9-oxide), a product initially isolated from extracts of garlic (Alium sativum), was tested for its antimalarial activity in vivo in a well-characterized murine model. A single ajoene dose of 50 mg/kg, on the day of infection, suppressed the development of parasitemia; there were no obvious acute toxic effects from the tested dose. The combination of ajoene (50 mg/kg) and chloroquine (4.5 mg/kg), given as a single dose on the day of the infection, completely prevented t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…lactone, Tagitinin C, present in the leaves of Tithonia diversifolia was active against Plasmodium falciparum (Goffin et al, 2002); (e) Ajoene, a metabolite of Allium sativum, was active against Plasmodium berghei in mice (Perez et al, 1994); (f) Simalikalactone D was identified to be responsible for the antimalarial activity of Quassia amara leaves (Bertani et al, 2006). However, the possibility that the in vitro data presented in the studies with these phytochemicals could be misleading cannot be overlooked because certain natural products are metabolized and the pharmacokinetics of the individual natural products are often totally ignored.…”
Section: Isolated Compounds Characterized As Antimalarials In Nigeriamentioning
confidence: 99%
“…lactone, Tagitinin C, present in the leaves of Tithonia diversifolia was active against Plasmodium falciparum (Goffin et al, 2002); (e) Ajoene, a metabolite of Allium sativum, was active against Plasmodium berghei in mice (Perez et al, 1994); (f) Simalikalactone D was identified to be responsible for the antimalarial activity of Quassia amara leaves (Bertani et al, 2006). However, the possibility that the in vitro data presented in the studies with these phytochemicals could be misleading cannot be overlooked because certain natural products are metabolized and the pharmacokinetics of the individual natural products are often totally ignored.…”
Section: Isolated Compounds Characterized As Antimalarials In Nigeriamentioning
confidence: 99%
“…Quinine isolated from Cinchona sp. bark and artimisinin from the Chinese plant Artimesia annua are established drugs against malaria (Agtmael et al, 1999;Perez et al, 1994). Apart from this currently cryptolepine derived from Cryptolepis sanguinolenta and tazospine purified from Madagascarian plant Strychnopsis thouarsii are potential antimalarial lead compounds (Cimanga et al, 1997;8, Carraz et al, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…Ajoenes metabolites ( 7) are a good example with the naturally occuring allicin that has proved to be active against rodent malaria and Trypanosoma cruzi. These sulfur containing aliphatics, initially isolated from garlic (Allium sativum, Liliaceae), showed significant suppression of Trypanosoma parasitemia in vivo with daily doses of 50 mg/kg over 12 days [37]. Gallwitz et al [38] identified ajoenes also as potential drugs effecting thiol metabolism by acting as a covalent inhibitor as well as a substrate of human glutathione reductase (GR) and secondly of the Trypanosoma cruzi trypanothione reductase (TR).…”
Section: Ajoenesmentioning
confidence: 99%